Emotional Intelligence in Small and Medium Entreprises: Exploring its Effect on Ambidextrous Behaviours and Firm Performance - Wai Chuen, Poon; Chan Yin-Fah, Benjamin; Kei Wei, Chia; Choon Jin, The (International Journal of Psychosocial Rehabilitation, 2020)
This paper contributes to the growing body of research that focuses on the antecedents of ambidextrous behaviours, that is, understanding the role of emotional intelligence influencing ambidextrous behaviours. One central challenge caused by ambidextrous behaviours is the divergence mindset catering to the contradiction of exploitative and explorative behaviours. The manner in which owner-managers recognize with and act out contradictory demands provides an insight into the balancing act of ambidextrous behaviours. Following theory of dynamic capability, the present paper simultaneously analyzes antecedents and consequences of ambidextrous behaviours. Regarding the antecedents, the present study sought to identify the dimensional roles of emotional intelligence (EI) influencing ambidextrous behaviours. With regard to consequences, the paper analyses the impact of ambidextrous behaviours on firm performance among owner-managers from small and medium enterprises (SMEs) in Kuala Lumpur and Selangor, Malaysia. Out of 1,000 invited respondents, a total of 220 owner-managers participated in this research. 183 useable data were analysed usingPartial Least Squares (SmartPLSv3.2.7), result indicates that all four dimensions of EI positively influence ambidextrous behaviours and there is a positive impact of ambidextrous behaviours on firm performance among SMES in Malaysia. This study adds to the limited theoretical and empirical understanding of the role of EI and ambidextrous behaviorus. This present study concludes by highlighting scope and significance of these findings for theory, managerial practice, and future research.